Sosialisasi Pemanfaatan Bunga Telang sebagai Peluang Usaha UMKM bagi Ibu Rumah Tangga di Desa Pohjejer - Ulfa Rahmawati; Idelfonsus Worong; Catur Puji Rahayu; Vivi Dwi Purwati; Nurur Rosyidah; Dias Destya Kharisma; Karromatul Mustika Permatasari; Mikho Janu Bactiar; Suci Firdaus; Moh. Miftakhuddin Zuhri; Titania Maynur Mahanani; Puput Fazria Novita Sari; Muhammad Iffan Ardani; Natswa Grasilia Wijaya; Siti Nur Asiyah; Achmad Faujzi; Muhajir Muhajir; Wulan Dewi; Dina Fitri Ana; Tahlia Eka Rafiti; Fenny Indrawanti; Ari Prabowo; Dhiba Daru Narendra; Tegar Ilmawan (Lembaga Pengembangan Kinerja Dosen, 2026)
The Impactfull Community Service Program (KKN) of Universitas Mayjen Sungkono in Pohjejer Village was conducted to optimize the utilization of butterfly pea flower (Clitoria ternatea) as a local resource that has not been fully utilized. The main problem faced by the community, particularly housewives, is the limited knowledge and skills related to the benefits, processing techniques, and business opportunities of butterfly pea flowers. This program aimed to enhance community knowledge and skills in processing butterfly pea flowers into herbal beverage products with economic value and the potential to be developed as home-based enterprises. The implementation methods included a community organizing approach, participatory socialization, interactive discussions, and direct demonstrations of herbal beverage production using butterfly pea flowers. The results indicated an improvement in participants’ understanding of the health benefits of butterfly pea flowers, appropriate processing methods, and their potential development as MSME products. In addition, the program increased participants’ interest and motivation to independently produce herbal beverages as an additional source of household income. Overall, this KKN program had a positive impact on encouraging the utilization of local resources to improve household economic conditions and empower rural communities.